THE ROLE OF DIGITAL TOURISM COMMUNICATION IN KASHMIR'S FINANCIAL ECONOMY: A NARRATIVE APPROACH - Sharma, Preeti; Sharma, Harshal (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the role of digital tourism communication in transforming the financial landscape of Kashmir’s tourism economy, with a focus on the integration of digital tools to promote economic development and regional narratives. Method: Utilizing a mixed-methods approach and a descriptive research design, quantitative surveys and qualitative interviews were conducted with 134 tourism business stakeholders, including hoteliers, travel agents, and handicraft sellers across major destinations such as Srinagar, Gulmarg, Pahalgam, and Sonmarg. Results: The findings reveal a high prevalence of digital engagement, particularly among younger entrepreneurs aged 18–35. Social media and online booking platforms are the most utilized, with 82.1% of respondents actively using digital tools and 94% perceiving a positive impact on the local economy. Despite challenges such as limited digital literacy and infrastructure gaps, stakeholders express optimism about digital tourism's future potential. Novelty: This study provides a localized and empirical insight into the intersection of digital innovation and tourism in a socio-politically sensitive region, highlighting the critical need for government intervention, capacity building, and sustainable tourism practices to achieve inclusive and long-term economic growth.